Construction of regional myths: a case study of the Greeks of the North Azov Sea region - Світлана Арабаджи (Cхід, 2023)
The article examines the process of constructing the mythological image of the Russian Empire as a "saviour of Christians" who were resettled from the Crimean peninsula to the North Azov Sea region, which became the basis for the formation of a historical myth in the region. The paper uses the analysis of various sources: orders, letters, reports, rescripts, descriptive and statistical materials, messages, etc. to consider the main stages of creating and maintaining this image and its articulation at different levels. The author proves that the positioning of Russia's special mission to protect the Christian population of the peninsula began from the moment the Russian Empire decided to resettle Christians from the territory of the Crimean Khanate. The Russian Empire assumed a leading role in the protection of “co-religionists” justifying themselves by unbearable religious oppression and the difficult situation of the Greeks, Armenians, Georgians and all those who practiced Orthodox Christianity in a Muslim state. To strengthen its role and emphasize the importance of its “mission” the Russian Empire created and spread the image of the Crimean Khanate as a despotic state that oppressed the Christian population in every possible way and limited their religious and social rights almost to the point of destruction. Their extremely difficult situation forced the Crimean Christians to appeal to the Russian Empress to resettle them on the territory of the Orthodox Empire. This was the official version of the resettlement of the Christians used at all levels and became the basis for the construction of the myth.